2009
DOI: 10.1080/01626620.2009.10463525
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Training of Teacher Educators

Abstract: Given that the numbers c, culturally andlor linguistically diverse StUMttS being educated in US. public schools are growing immensely, teacher educators must take responsibility for preparing teacher candidates to work in today's diverse classrooms. This can be difficult, however, if teacher educators are not culturally responsive in their curricular content and pedagogy. Teacher educators could benefit from engaging in professional development in this area. In this article, we discuss the professional literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…In this article, I define cultural identity as one's relationship to language, age, race, sexuality, socioeconomic class, religion, and gender (Banks, 2006). One aspect of fostering a culturally responsive pedagogy is for teachers to value the different cultures that are represented in the classroom, have an understanding of the different way their students relate to their cultural identities, and infuse knowledge about their students' culture into the curriculum (Prater & Devereaux, 2009).…”
Section: Detra Price-dennis Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, I define cultural identity as one's relationship to language, age, race, sexuality, socioeconomic class, religion, and gender (Banks, 2006). One aspect of fostering a culturally responsive pedagogy is for teachers to value the different cultures that are represented in the classroom, have an understanding of the different way their students relate to their cultural identities, and infuse knowledge about their students' culture into the curriculum (Prater & Devereaux, 2009).…”
Section: Detra Price-dennis Editormentioning
confidence: 99%
“…(Edwardson, 2011, p. 1) T he excerpt above is from the multicultural young adult book, My Name Is Not Easy (Edwardson, 2011). This powerful book explores the disconnect between adolescent identity, home culture, and school practices, examining the message many students hear that assimilation is important to the detriment of personal culture and identity (Souto-Manning, 2011). As a classroom teacher and now a teacher educator, I have seen the re-naming of students by parents, teachers, and by students themselves.…”
mentioning
confidence: 98%
“…In recent years, even though the border has seen major changes in enforcement and policy of immigrant entry (Martin, 2017), the number of culturally and linguistically diverse students being taught in U.S. schools are growing at a significant rate (Prater & Devereaux, 2009). For example, the majority of entrants through the U.S./Mexico border are displaced persons and refugees from Latin American countries, resulting from drug cartel violence (UNHCR, 2009).…”
Section: Issues Facing Displaced Latinx Youthmentioning
confidence: 99%
“…Creating a culturally relevant curriculum is of the utmost importance for students of color in the U.S. Prater and Devereaux (2009) assert that a culturally competent teacher can "infuse cultural knowledge and adapt their curricula and pedagogy to the dynamics of differences in the classroom" (p. 20). For Latinx students to be successful in school, it is essential that they are represented in their classroom content.…”
Section: Unpacking a Culturally Relevant Pedagogymentioning
confidence: 99%
“…Research has shown that the distinct experiences and unique backgrounds brought to the college classroom by a diverse student body enhance the educational outcomes of all students (Gurin, Dey, Hurtado, & Gurin, 2002;Milem, Chang, & Antonio, 2005). As such, there is a need for professional development opportunities that support faculty members in embracing diversity as an asset and in becoming more culturally responsive in their teaching (Barrington, 2004;Gay, 2018;Marchesani & Adams, 1992;Powell, Cantrell, Malo-Juvera, & Correll, 2016;Prater & Devereaux, 2009;Villegas & Lucas, 2002). Inclusive pedagogy interventions, such as workshops, have been shown to help faculty be more intentional in their efforts to select content and incorporate instructional strategies that leverage the educational benefits of diverse classrooms (Booker, Merriweather, & Campbell-Whatley, 2016).…”
Section: Introductionmentioning
confidence: 99%